ENTERAL NUTRITION IN SEPSIS: CAN WE BREAK THE MYTH? - Stojanovic, Milena (Acta medicae Medianae, 2025)
Sepsis is a complex disorder that occurs as a result of the host’s inadequate response to infection, and it is associated with acute organ failure and a high mortality rate. Over the past 30 years lot of research has been conducted in this field, which resulted in a faster recognition of the septic patient by using adequate scores and changing the existing ones. Septic shock is defined as hypotension despite adequate fluid resuscitation, therefore requires vasopressor support and is accompanied by circulatory, metabolic and cellular abnormalities.Sepsis and septic shock are typically associated with catabolic stress, where patients exhibit a systemic inflammatory response associated with complications such as multiorgan dysfunction, morbidity, prolonged hospitalization and death. Malnutrition is common in septic patients, taking into account pronounced catabolism in the early phase. In septic patients, enteral nutrition can be important for covering the energy requirements. Early nutrition therapy, primarily by enteral route, is today seen as a proactive therapeutic strategy with the aim of reducing the severity of the disease, complications, length of hospital stay and positive outcome of the patient.Enteral nutrition should not be started in patients who are hypotensive (MAP < 50 mmHg), in whom treatment with vasopressors has just started or in whom there is an escalation of vasopressor doses. According to recommendations, enteral nutrition should be withheld until hemodynamic stability is achieved. The risks and benefits of enteral nutrition must be considered for each patient in the state of septic shock. Noradrenaline dose of < 0.3 mcg/kg/min can be considered safe, and such patients can be characterized as hemodynamically stable.
Keywords: sepsis, septic shock, enteral nutrition, vasopressors, noradrenaline